Motivation of labour activity as a determinant of the succesful vocational formation of a personality - Rubaževičienė, M. (Psichologija, 1988)
The results of the study of certain features of labour motivation and tendencies of its change curing the first year of practical occupation are presented. The investigation of labour motives made it possible to predict deficiencies in the vocational formation of young women-workers at the initial period of their occupational activities.
Keywords: Motivation of Labour Activity; Successful Vocational Formation